Existence de solutions de quelques problèmes elliptiques. - Mohamed Khelaifia (My University, 2025)
In this work, we study nonlinear elliptic equations in bounded open sets. We introduce some functional concepts. We demonstrate the existence of solutions in Sobolev spaces by applying the principles of the mountain pass theorem. We begin by studying a linear elliptic problems of the form : -Δu=f in Ω with Ω a bounded open set and f∈L²(Ω), using the Lax-Milgram theorem, we prove the existence of a unique solution with different boundary conditions. Next, we study a problem of the form : -div(a(x,∇u))=f(x,u) in Ω u=0 on ∂Ω where Ω a bounded open set of ℝⁿ. We prove the existence of at least one solution by showing that the associated energy functional satisfies the mountain pass geometry. ---------------------------------------------------------------------- في هذا العمل، قمنا بدراسة المعادلات الإهليلجية غير الخطية في المجموعات المفتوحة المحدودة. نقدم بعض المفاهيم الوظيفية . نظهِر وجود الحلول في فضاءات سوبوليف . من خلال تطبيق مبادئ نظرية ممر الجبل . نبدأ بدراسة المسائل الإهليلجية الخطية من النموذج : -Δu=f فى Ω حيث Ω مجموعة مفتوحة محدودة و f∈L²(Ω) ، وباستخدام نظرية لاكس-ميلجرام، نظهر وجود حل وحيد مع مختلف الشروط الحدية. بعد ذلك، ندرس مسألة من الشكل : -div(a(x,∇u))=f(x,u) في Ω u=0 على ∂Ω مع Ω مجموعة مفتوحة محدودة من ℝⁿ . نثبت وجود حل واحد على الأقل من خلال إظهار أن الدالة الوظيفية للطاقة المرتبطة تلبي هندسة ممر الجبل --------------------------------------------------------------------------- Dans ce travail, nous étudions des équations elliptiques non linéaires dans des ouverts bornés. Nous introduisons quelques notions fonctionnelles. Nous montrons l'existence des solutions dans les espaces de Sobolev en appliquant des principes le théorème de passe montagne. Commençons par étudier des problèmes elliptiques linéaires de la forme : -Δu=f dans Ω avec Ω un ouvert borné et f∈L²(Ω), par le théorème de Lax-Milgram, nous montrons l'existence d'une solution unique avec les différentes conditions aux bords. Ensuite, nous étudions un problème de la forme : -div(a(x,∇u))=f(x,u) dans Ω u=0 sur ∂Ω avec Ω un ouvert borné de ℝⁿ Nous prouvons l'existence d'au moins une solution par montrer que la fonctionnelle d'énergie associée vérifie la géométrie de passe montagne.
Keywords: elliptic problems; mountain pass theorem; Sobolev spaces; Palais-Smale condition; Lax-Milgram theorem.; مسائل إهليلجية، نظرية ممر الجبل، فضاءات سوبوليف، شرط بالي-سمال، نظرية لاكس-ميلجرام .; problèmes elliptiques; théorème de passe montagne; espaces de Sobolev; condition de Palais-Smale; théorème de Lax-Milgram.